2021
DOI: 10.2196/30322
|View full text |Cite
|
Sign up to set email alerts
|

Sociotechnical Drivers and Barriers in the Consumer Adoption of Personal Health Records: Empirical Investigation

Abstract: Background Increasingly popular in the health care domain, electronic personal health records (PHRs) have the potential to foster engagement toward improving health outcomes, achieving efficiencies in care, and reducing costs. Despite the touted benefits of PHRs, their uptake is lackluster, with low adoption rates. Objective This paper reports findings from an empirical investigation of the sociotechnical factors affecting the adoption of PHRs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 123 publications
(196 reference statements)
0
3
0
Order By: Relevance
“…The literature on PHR has indicated that adoption barriers may be linked to technology factors such as security concerns, system usability, and ineffective healthcare provider system integration [37,41,[59][60][61]. Several personal factors have also been articulated as barriers to adopting these technologies, such as lack of technology awareness, competency, chronic medical conditions, and unrealistic expectations [41,57,[61][62][63][64][65].…”
Section: Literature Review Phr Adoptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on PHR has indicated that adoption barriers may be linked to technology factors such as security concerns, system usability, and ineffective healthcare provider system integration [37,41,[59][60][61]. Several personal factors have also been articulated as barriers to adopting these technologies, such as lack of technology awareness, competency, chronic medical conditions, and unrealistic expectations [41,57,[61][62][63][64][65].…”
Section: Literature Review Phr Adoptionmentioning
confidence: 99%
“…The reviewed relevant studies show that chronically ill or disabled patients and their caregivers and older people's caregivers have a higher likelihood of adopting and using PHR technologies [70][71][72][73]. This user group often views PHR technologies as useful in communicating with the correct personnel to obtain personalised care [37,71,74].…”
Section: Literature Review Phr Adoptionmentioning
confidence: 99%
See 1 more Smart Citation